Implementation of Character Education in Learning Natural and Social Sciences in Grade IV Elementary Schools - Cahyadi, Oktariana Putri; Hidayat, Otib Satibi; Karsih (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2025)
Social Sciences (IPS) and Natural Sciences (IPA) are subjects that play a role important to form inhabitant country Which good in a nation. Therefore , learning Knowledge Social Studies and Natural Sciences are very much needed in schools, especially at the higher education level. basic, where basic education is the foundation of understanding and science about how to live socially in the community environment. This research aiming For to obtain Implementation Learning Social Sciences and Natural Sciences towards formation character students in i School Base. By using the literature study research method. The results of this study can know the character is an individual's nature, personality, character and behavior someone in someone's life. Character is a major aspect in to form the quality of a person to become a noble person. To produce participants educate Which quality, namely a person who is able to think critically, creatively, logically and take the initiative in facing problems symptom And social problems Which develop in society, Natural and Social Sciences (IPAS) education has a very important role.